MicroRNAs in blood act as biomarkers of colorectal cancer and indicate potential therapeutic targets. Issue 9 (5th August 2021) - Stang, Axel; Weilert, Hauke; Lipp, Michael J.; Oldhafer, Karl J.; Hoheisel, Jörg D.; Zhang, Chaoyang; Bauer, Andrea S.
Abstract : Association studies have linked alterations of blood‐derived microRNAs (miRNAs) with colorectal cancer (CRC). Here, we performed a microarray‐based comparison of the profiles of 2549 miRNAs in 80 blood samples from healthy donors and patients with colorectal adenomas, colorectal diverticulitis and CRC at different stages. Confirmation by quantitative real‐time PCR (RT‐PCR) was complemented by validation of identified molecules in another 36 blood samples. No variations in miRNA levels were observed in samples from patients with colorectal adenomas and diverticulitis or from healthy donors. However, there were 179 CRC‐associated miRNAs of differential abundance compared to healthy controls. Only three – miR‐1225‐5p, miR‐1207‐5p and miR‐4459 – exhibited increased levels at all CRC stages. Most deregulated miRNAs (128/179, 71%) specifically predicted metastatic CRC. Pathway analysis found several cancer‐related pathways to which the miRNAs contribute in various ways. In conclusion, miRNA levels in blood vary throughout CRC progression and affect cellular functions relevant to haematogenous CRC progression and dissemination. The identified biomarker and therapeutic candidates require further confirmation of their clinical relevance. Abstract : Here, we performed a comprehensive study on the abundance variations of 2549 miRNAs in blood from 80 healthy donors and patients with colorectal disease. We further validated the results in 36 independent samples by quantitative real‐time PCR. Patients with colorectal adenomas or diverticulitis and healthy donors exhibited no difference in their miRNA profiles, while patients with colorectal cancer displayed miRNAs with differential abundance in a stage‐specific manner. The miRNAs identified in our study contribute to several cancer‐related pathways relevant to colorectal cancer progression and haematogenous dissemination.